Земная колыбель: стихи раз лет / Сергей Поделков ; художник И. С. Клейнард - Поделков Сергей Александрович (Советская Россия, 1984)
Экземпляры: Аб (1984) / Инвентарный номер: 6845 / Авт.знак: П 44 / ГРНТИ: 17.82.10 / ББК: 84(2Pос=Рус)6